2019
DOI: 10.1177/8756972819870357
|View full text |Cite
|
Sign up to set email alerts
|

Project Lineage Management and Project Portfolio Success

Abstract: Project portfolio approaches consider various concurrent project interdependencies but typically neglect longitudinal interdependencies. These are important for exploratory projects, which create strategic options. If these options are not exploited in successive projects they become lost opportunities. This study analyzes 138 firms regarding their extent to consciously manage project sequences. We differentiate between proactive lineage (planning a roadmap of future projects) and reactive lineage (using learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…While previous strategic literature on entrepreneurial orientation has mainly considered its direct influence (Wales et al, 2013), this article offers additional insight into entrepreneurial orientation's organizational support. Further, we add to recent literature on adaptiveness in new product development (Cooper & Sommer, 2016; Kock & Gemünden, 2016, 2019). In combination with frequent portfolio reviews, ROR constitutes a suitable approach for firms to increase their innovativeness, which enables them to better adapt to future challenges (Kogut & Kulatilaka, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…While previous strategic literature on entrepreneurial orientation has mainly considered its direct influence (Wales et al, 2013), this article offers additional insight into entrepreneurial orientation's organizational support. Further, we add to recent literature on adaptiveness in new product development (Cooper & Sommer, 2016; Kock & Gemünden, 2016, 2019). In combination with frequent portfolio reviews, ROR constitutes a suitable approach for firms to increase their innovativeness, which enables them to better adapt to future challenges (Kogut & Kulatilaka, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…We showed that decision-makers apply ROR in the development process of health estate projects. Thus, our research builds on [11],…”
Section: Discussionmentioning
confidence: 99%
“…ROR enables decision-makers to develop infrastructure able to accommodate changing requirements throughout its operational life [8], [9]. ROR highlights the benefit of managerial flexibility under uncertainty [5], [7] and how flexibility influences value creation [10], [11]. ROR is useful when decision-makers cannot quantify the value of operating different options, either because the information in unreliable or not obtainable, or the firm does not have the required resources and capabilities [12].…”
Section: Introductionmentioning
confidence: 99%
“…The latter performance dimensions can also be impacted by the proficiency of downstream activities such as launch and sales activities or postlaunch moves of competitors. That being said, project success metrics are neither fully decoupled from market characteristics nor overall innovation program performance (Kock & Gemünden, 2019). Faster changing customer needs can trigger to change project requirements and thereby affect the time and budget necessary to adapt to the changed requirements.…”
Section: Limitations and Future Researchmentioning
confidence: 99%